Silica SOS@HKUST-1 composite microspheres as easily packed stationary phases for fast separation - Ahmed, Adham; Forster, Mark; Clowes, Rob; Bradshaw, Darren; Myers, Peter; Zhang, Haifei (Journal of materials chemistry. A, Materials for energy and sustainability, 2013)
Metal–organic frameworks (MOFs) have been investigated for separations including chromatography. Typically, MOF particles are directly packed into columns for the separations. The irregular shapes and wide size distributions of MOF particles have led to difficulty in column packing and low column efficiency or high back pressure. We describe here the preparation of MOF–silica microspheres as packing materials for fast and efficient liquid chromatography. Spheres-on-sphere (SOS) silica particles are prepared, modified with –COOH and –NH₂ groups, and then used as support to grow HKUST-1. HKUST-1 nanocrystals and films are formed and attached firmly onto the SOS particles with adjustable porosity. The composite microspheres, showing core–shell properties, are directly packed into columns to offer separation capability of MOFs and efficient packing and support of silica microspheres. These columns show separation of toluene/ethylbenzene/styrene and toluene/o-xylene/thiophene within 1.5 minutes. Although HKUST-1 is not good for separating xylene isomers, the separation can be achieved in 5 minutes using the composite microspheres after conditioning the column with dichloromethane or toluene. Remarkably, it is observed that conditioning with DCM can change retention time and selectivity (elution order) of xylene isomers. It is also possible to produce other types of MOFs (e.g., ZIF-8) on the SOS particles, indicating the potential of this method for wider applications.